Nutritional and antibacterial properties of yeast-fermented herbs for functional poultry feeds - Malahubban, Masnindah; Kamaludeen, Juriah; Mustafa, Suhaili; Hanafiah, Muhamad Hakim Mohd Ali; Barudi, Maria Eva; Zakry, Fitri Ab Aziz (Journal of Phytology, 2025)
This study assesses the nutritional and bactericidal characteristics of yeast-fermented herbs as prospective substitutes for antibiotics in animal feed. A fermentation process was conducted on five plants, namely Syzygium polyanthum, Curcuma longa, Andrographis paniculata, Orthosiphon stamineus, and Euphorbia hirta, using Saccharomyces cerevisiae. Analysis conducted after fermentation showed notable alterations in the nutritional composition, with a rise in protein content and a decline in carbohydrate levels. The mineral profiling revealed fluctuations in nutrient contents, particularly significant increases in nitrogen and phosphorus. The antibacterial assays showed that fermented herbs were more effective against bacteria isolates, Escherichia coli, Streptococcus gallolyticus, Staphylococcus aureus, and Aeromonas hydrophila, than non-fermented herbs. The study found that fermented Curcuma longa has a similar antibacterial effectiveness as tetracycline, making it a potential alternative antimicrobial agent in animal feed. The study reveals that yeast-fermented herbs might be a viable and efficient substitute for antibiotics in poultry production, while also being environmentally friendly.